Nidos de Cardenal Amarillo (Gubernatrix cristata) en la provincia de San Luis, Argentina - Domínguez, Marisol; Ayarragaray, Matias; Lapido, Rocío (Nuestras Aves, 2015)
Este artículo no cuenta con un resumen.